Hong Kong election reform : will it happen? - Loh, Dylan Ming Hui (2015)
The Hong Kong government’s election reform proposal would, in theory, allow for greater flexibility and competition for the 2017 race for Chief Executive. However, with pan-democratic lawmakers vowing to veto the proposal, what are the chances of the ‘one person one vote’ elections happening?